Multiphase flow simulation in injection pultrusion with variable properties. Issue 2 (25th January 2020) - Tucci, Fausto; Bezerra, Renato; Rubino, Felice; Carlone, Pierpaolo
ABSTRACT: This paper presents a multiphase approach to the simulation of the fiber impregnation in injection pultrusion processes. The computational fluid dynamics model, implemented and solved in the Ansys-CFX environment, accounts for the presence of two distinct fluid phases, namely resin and air, and for the influence of temperature distribution in the injection chamber on the fluids' viscosity and density. Numerical outcomes were compared with experimental data collected on an injection pultrusion line equipped with pressure transducers, thermocouples, encoder, and a load cell. Two different pulling speeds, 300 and 500 mm/min, were set to pultrude a rectangular section profile made of epoxy resin and E-glass fiber rovings. Simulation predictions for the pressure development and void fraction were in agreement with experimental observations, when the thermal effects in the properties were taken into account, whereas computations based on simplified assumptions were affected by unacceptable errors in the estimation of pressure and void fraction.